2015
DOI: 10.4081/aiua.2015.3.204
|View full text |Cite
|
Sign up to set email alerts
|

PDE-5 inhibitors in monotherapy versus combination therapy in a sample of 1200 patients with erectile dysfunction

Abstract: Objectives: To compare the effectiveness in the treatment of erectile dysfunction when using PDE-5 inhibitors (PDE5i), alprostadil (PG-E1) and testosterone (TES) in SummaryNo conflict of interest declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The last cohort study, a retrospective analysis, evaluated PDE5i monotherapy versus PDE5i and PG‐E1. Monotherapy had substantially increased patient satisfaction as compared to combination therapy [ 14 ] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The last cohort study, a retrospective analysis, evaluated PDE5i monotherapy versus PDE5i and PG‐E1. Monotherapy had substantially increased patient satisfaction as compared to combination therapy [ 14 ] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Questions of combination therapy superiority are not limited to oral medications. Labairu‐Huerta et al [ 14 ] evaluated the efficacy of a variety of combination therapies, including PGE1 and PDE5i. A total of 1200 men were included in the study, with patients split between the monotherapy and combination therapy groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic science literature has confirmed the necessity of androgens to generate adequate intracavernosal pressures and smooth muscle function to obtain an erection [59]. The literature showing the impact of testosterone replacement therapy (TRT) on erectile function is quite heterogenous (Table 1) [6061626364656667686970717273747576777879808182838485868788899091]. A subset analysis of the Olmstead County Cohort published by Gades et al [92] showed that testosterone has a statistically significant positive correlation with erectile function, even when adjusted for age.…”
Section: Hypogonadismmentioning
confidence: 99%